Theatre and cartographies of power : repositioning the Latina/o Americas - Noriega, Jimmy A.; Santana, Analola (Theater in the Americas., 2018)
"This book reconsiders and redefines the ways in which theatrical and performance histories have been constructed and disseminated throughout the Americas"--